Increasing Nurses' Affective Professional Commitment through Person Job-Fit - Praptini Yulianti; Noorlaily Fitdiarini (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: The nurses must have an affective professional commitment to do their job. They must be competent and have more emotional response to caring for the patients. This study aims to develop affective professionals commitment through job-fit in two perspectives: demand-abilities perspective (DA-fit) and supply-value perspective (SV-fit). Design/Methods/Approach: The sample consisted of 187 nurses that collected through simple random sampling techniques in a private hospital in Surabaya. This study employs SmartPLS 3.0 program to analyze the data. Findings: The results indicate that Person Job-fit (DA-fit) has positive and significant relationship with self-efficacy. Person Job-fit (SV-fit) has positive and significant effect on job satisfaction. Self-efficacy and job satisfaction have positive and significant influence to affective professional commitment. Originality: This study focuses on the general person-job fit and examines person job fit from DA-fit and SV-fit perspectives separately Practical implication: The recruitment process should consider nurses' passion for work and competency.